Polygyny is linked to accelerated birdsong evolution but not to larger song repertoires - Kate T. Snyder (Nature Portfolio, 2019)
Sexual selection is expected to be intensified in non-monogamous mating systems; in birds this might accelerate song evolution. Here, the authors show that across songbirds, polygyny and extra-pair paternity are associated with faster syllable repertoire size evolution and smaller repertoire size, respectively.